Forge: the f(R)-gravity cosmic emulator project – I. Introduction and matter power spectrum emulator. Issue 3 (10th August 2022) - Arnold, Christian; Li, Baojiu; Giblin, Benjamin; Harnois-Déraps, Joachim; Cai, Yan-Chuan
ABSTRACT: We present a large suite of cosmological simulations, the forge (F-of-R Gravity Emulator) simulation suite, which is designed to build accurate emulators for cosmological observables in galaxy clustering, weak gravitational lensing, and galaxy clusters for the f ( R )-gravity model. A total of 200 simulations explore the cosmological parameter space around a standard Planck cosmology with a Latin hypercube, for 50 combinations of $\bar{f}_{R0}$, Ωm, σ8, and h with all other parameters fixed. For each parameter combination, or node, we ran four independent simulations, one pair using 1024 3 particles in $500\, h^{-1}\, Mpc$ simulation boxes to cover small scales, and another pair using 512 3 simulation particles in $1.5\, h^{-1}\, Gpc$ boxes for larger scales. Each pair of initial conditions is selected such that sample variance on large scales is minimized on average. In this work we present an accurate emulator for the matter power spectrum in f ( R ) gravity trained on forge . We have verified, using the cross-validation technique, that the emulator accuracy is better than $2.5{{\, \rm per\, cent}}$ for the majority of nodes, particularly around the centre of the explored parameter space, up to scales of $k = 10\, h \, Mpc^{-1}$ . We have also checked the power spectrum emulator against simulations that are not part of our training set and found excellent agreement. Due to its high accuracy on small scales, the forge matter power spectrum emulator is well suited for weak-lensing analysis and can play a key tool in constraining f ( R ) gravity using current and future observational data.